Genetic Risk Factors for Alzheimer's Disease in Racial/Ethnic Minority Populations in the U.S.: A Scoping Review - Rubin, Lindsey; Ingram, Lucy A.; Resciniti, Nicholas V.; Ashford-Carroll, Brianna; Leith, Katherine Henrietta; Rose, Aubrey; Ureña, Stephanie; McCollum, Quentin; Friedman, Daniela B. (Frontiers in Public Health, 2021)
Objectives: As the U.S. population rapidly ages, the incidence of Alzheimer’s Disease and Related Dementias (ADRDs) is rising, with racial/ethnic minorities affected at disproportionate rates. Much research has been undertaken to test, sequence and analyze genetic risk factors for ADRDs in Caucasian populations, but comparatively little has been done with racial/ethnic minority populations. We conducted a scoping review to examine the nature and extent of the research that has been published about the genetic factors of ADRDs among racial/ethnic minorities in the U.S. Design: Using an established scoping review methodological framework, we searched electronic databases for articles describing peer-reviewed empirical studies or Genome-Wide Association Studies that had been published 2005-2018 and focused on ADRD-related genes or genetic factors among underrepresented racial/ethnic minority population in the U.S. Results: Sixty-six articles met the inclusion criteria for full text review. Well-established ADRD genetic risk factors for Caucasian populations including APOE, APP, PSEN1 and PSEN2 have not been studied to the same degree in minority U.S. populations. Compared to the amount of research that has been conducted with Caucasian populations in the U.S., racial/ethnic minority communities are underrepresented. Conclusion: Given the projected growth of the aging population and incidence of ADRDs, particularly among racial/ethnic minorities, increased focus on this important segment of the population is warranted. Our review can aid researchers in developing fundamental research questions to determine the role that ADRD risk genes play in the heavier burden of ADRDs in racial/ethnic minority populations.